Las demandas del agronegocio y los pequeños núcleos urbanos del sur de Córdoba (Argentina) - Picciani, Ana Laura (2023)
This article analyzes the role that the city of Río Cuarto acquires within the agricultural production network of southern Cordoba, as it has an important link with the agribusiness model. This is based on the analysis of the relationship between the agricultural support service companies installed in the city and their articulation with the companies installed in other urban centers of the department of Río Cuarto. The foregoing is based on semi-structured interviews with key actors in agribusiness (multinational suppliers of inputs for agriculture) present in the study area.